Capital Account Liberalization and the Politics of Access to Finance in Latin America. Issue 5 (19th October 2016) - Yoo, Daniel
ABSTRACT: Does capital account liberalization improve access to finance? A rich body of evidence suggests that it does, but there are many empirical discrepancies to this relationship, especially in Latin America. When the financial sector is highly concentrated, the incentives of banks and governments are aligned to enlarge the opportunities to gain from financial openness by suppressing policies that reform the domestic financial sector. The result is that capital account liberalization that occurs in such a context should improve access to credit for governments but impede access to credit among private firms and households.